Will Bulgaria's Path to Eurozone Derail? A comparison with Argentina (Journal of Entrepreneurship and Business, 2021)
In the wake of the prospects of Bulgaria joining the Euro area and the recent Eurozone crisis, it is pertinent to find out how parallel are the circumstances faced by the recent Bulgaria with the conditions of the then Argentina whose currency board had to be abandoned. In a nutshell, this paper compares Bulgaria in 2000-20101 to Argentina in 1991-2001, the period of the Argentine convertibility system. The dimensions explored are (1) adherence to currency board principles, (2) performance indicators associated with exchange rate fixity, and (3) conformity to the criteria inspired by the optimum currency areas (OCA) theory. Raw data are sourced from credible international organizations while computed data are analyzed using charts. On the whole, Bulgaria does bear a resemblance to Argentina and this poses a hindrance to the sustainability of its currency board system and to its hope for Eurozone accession.
Keywords: Array; Array; Array; Array; Array; Array; Array